The Reaction Of The Indonesian Capital Market When Indonesia Experiences Recession In 2020 : Reaksi Pasar Modal Indonesia Pada Saat Indonesia Mengalami Resesi Tahun 2020 - Rony Yulian Putra Santoso; Heri Widodo (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to explain whether or not there is evidence of differences in abnormal return, trading volume activity, and security return variability of companies listed in the LQ45 index on the IDX before and after the November 2020 recession announcement. This study uses quantitative research approach. The LQ45 index is the research population used in this study. Meanwhile, to determine the research sample in this study using purposive sampling technique. The Wilcoxon Signed Rank Test is a data analysis technique used. Based on the results of the research, the abnormal return indicator gives a change with sig. 0.012. Trading volume activity changes with sig. 0.000. Security return variability provides changes with the value of sig. 0.026. So it can be concluded that in the event of an announcement of a recession there is a capital market reaction to companies listed in the LQ45 index.